Pernikahan Dibawah Umur Dalam Perspektif Hadis Bukhari 5134: Analisis Implementasi Pasal 7 UU No 16 Tahun 2019 - Nabilla Fitri Arfian; arifin, tajul (STIS DAFA MATARAM, 2025)
This research examines the influence of understanding Hadith Bukhari No. 5134 on minimum marriage age perspectives and the implementation of Article 7 of Law No. 16 of 2019 regarding child marriage in Indonesia. Using a normative juridical approach through literature study, this research analyzes hadith texts, laws, and related literature. Results show that Hadith Bukhari No. 5134 must be understood within the historical context of 7th-century Arabia and aligned with Quranic principles of physical-mental readiness. Implementation of Law No. 16 of 2019, which raised the marriage age to 19, remains ineffective due to high marriage dispensations and limited socialization. Child marriage factors include economic hardship, low education, socio-cultural norms, lack of reproductive education, and out-of-wedlock pregnancy. Impacts include reproductive health disorders, psychological issues, educational disruption, and perpetual poverty. Solutions require holistic approaches involving various parties through law enforcement, education, and economic empowerment.